Recent progress of atmospheric and room‐temperature plasma as a new and promising mutagenesis technology - Li, Dongao; Shen, Jie; Ding, Qiang; Wu, Jinyong; Chen, Xiangsong (Cell biochemistry and function, 2024)
At present, atmospheric and room‐temperature plasma (ARTP) is regarded as a new and powerful mutagenesis technology with the advantages of environment‐friendliness, operation under mild conditions, and fast mutagenesis speed. Compared with traditional mutagenesis strategies, ARTP is used mainly to change the structure of microbial DNA, enzymes, and proteins through a series of physical, chemical, and electromagnetic effects with the organisms, leading to nucleotide breakage, conversion or inversion, causing various DNA damages, so as to screen out the microbial mutants with better biological characteristics. As a result, in recent years, ARTP mutagenesis and the combination of ARTP with traditional mutagenesis have been widely used in microbiology, showing great potential for application. In this review, the recent progress of ARTP mutagenesis in different application fields and bottlenecks of this technology are systematically summarized, with a view to providing a theoretical basis and technical support for better application. Finally, the outlook of ARTP mutagenesis is presented, and we identify the challenges in the field of microbial mutagenesis by ARTP. Significance statement The aim of this review is to analyze the beneficial mutagenic effects induced by ARTP on microbial cells and the related mutagenic mechanisms. Subsequently, bottleneck issues and the recent research progress of ARTP on mutagenesis are systematically summarized, and the application prospect is presented. This review may provide valuable insights and research ideas for future atmospheric and room‐temperature plasma mutagenesis of cells.